Diagnostic Accuracy of Harbinger Score by Comparing It with Glasgow Blatchford (GBS) for Prediction of Early Endoscopic Intervention Need in Patients with Upper Gastrointestinal Bleed (UGIB): Diagnostic Accuracy of Harbinger Score - Rehan, Bushra; ul Haq, Muhammad Mansoor; Wadwa, Rajesh Kumar (Pakistan Journal of Health Sciences, 2023)
Accurate risk assessment techniques are crucial to aid in clinical decision-making on the need for early endoscopic intervention in patients with upper GI bleed. The Glasgow-Blatchford Score and the Harbinger Score are two popular scoring systems; however, it is uncertain how accurate their comparative diagnostic abilities are. Objective: To evaluate and compare the diagnostic precision of the Harbinger Score and the Glasgow-Blachford Score in determining the need for early endoscopic intervention among patients experiencing upper gastrointestinal bleeding (UGIB). Methods: 278 UGIB patients who came to the Department of Gastroenterology, Liaqat National Hospital, Karachi, between July 2022 and June 2023 were enrolled. Demographic, clinical information and scores for Harbinger and Glasgow-Blatchford rating systems were derived for each patient. Outcome measure was the requirement for early endoscopic intervention. Diagnostic accuracy was determined and contrasted for both scoring systems. Results: 192 (69.06%) were male, 86 (30.93%) female. Age ranged from 16 to 80 years, with a mean of 65.5±16.4. 117 patients (42.08%) presented with dyspepsia and heartburn and syncope in 6 (2.15%). Mortality AUC was 0.761 for GBS and 0.532 for Harbinger score, p-value <0.002. Both Harbinger and GBS scored >14 and 1. GBS specificity was 88% and Harbinger 54%, while susceptibility was 80% (90% CI: 35.9-95.8) for both scores. The intensive care AUC was 0.769 for GBS and 0.531 for Harbinger score, with a p-value <0.002. Conclusions: According to this study, Harbinger score had better sensitivity than GBS for predicting upper GI bleeding.